2015
DOI: 10.1590/1982-43272560201512
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Crisis Management in the Emergency Care Hospital Network

Abstract: Since psychiatric crisis treatment is crucial in mental health care, this study aimed to characterize the psychiatric crisis in the hospital emergency services of Natal/RN. Semi-structured interviews were conducted with 33 professionals employed in four local public hospitals. The results revealed the absence of adequate beds for psychiatric conditions, scarcity of psychiatric drugs, lack of clarity regarding diagnostic criteria, treatment based on chemical restraint and inpatient care as a priority strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…In addition to an inadequate welcoming by health professionals, it was observed the disarticulation of the services that make up the Psychosocial Care Network and the systematic referral to the psychiatric hospital as a priority strategy. 42 The role of hospital-centered care was also detected in the present study, since in 91.6% of the cases the users were referred to the psychiatric hospital. This reality is contrary to the principles of the psychiatric reform, since it favors care in general hospitals or other community-based extra-hospital mental health services.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to an inadequate welcoming by health professionals, it was observed the disarticulation of the services that make up the Psychosocial Care Network and the systematic referral to the psychiatric hospital as a priority strategy. 42 The role of hospital-centered care was also detected in the present study, since in 91.6% of the cases the users were referred to the psychiatric hospital. This reality is contrary to the principles of the psychiatric reform, since it favors care in general hospitals or other community-based extra-hospital mental health services.…”
Section: Discussionsupporting
confidence: 62%
“…According to study participants, there are resistances and barriers to the care of people with mental disorders in nonspecialized services, which strengthens the focus on specialties. The reports emphasized difficulties to meet urgent and emergency care, a topic addressed in other studies (10,36) . A study involving 156 workers from different regions of the country enrolled in the course "Crisis and Urgency in Mental Health", offered in partnership by a federal university and the Ministry of Health, revealed that care was provided primarily with drugs, mechanical containment and hospitalization (10) .…”
Section: Discussionmentioning
confidence: 95%
“…A study involving 156 workers from different regions of the country enrolled in the course "Crisis and Urgency in Mental Health", offered in partnership by a federal university and the Ministry of Health, revealed that care was provided primarily with drugs, mechanical containment and hospitalization (10) . This highlights the importance of strengthening the action in network and investing in continuing education to consolidate care and overcome the centrality of the psychiatric hospital in crisis management (10,36) . Nevertheless, previous studies have problematized the idea that the solution to most limitations in the field of mental health is training (22,37) , since even among some highly specialized teams, such limits are present.…”
Section: Discussionmentioning
confidence: 99%